2013
DOI: 10.1016/j.scr.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-5p and miR-106a are involved in the balance between osteogenic and adipogenic differentiation of adipose-derived mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) can differentiate into several distinct cell types, including osteoblasts and adipocytes. The balance between osteogenic and adipogenic differentiation is disrupted in several osteogenic-related disorders, such as osteoporosis. So far, little is known about the molecular mechanisms that drive final lineage commitment of MSCs. In this study, we revealed that miR-17-5p and miR-106a have dual functions in the modulation of human adipose-derived mesenchymal stem cells (hADSCs) commitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 55 publications
3
95
0
Order By: Relevance
“…hADSCs in the third passage were used for the following experiments. Adipogenic and osteogenic differentiation of hADSCs was performed as described earlier [23,24]. hADSCs from three different individuals were used as biological replicates.…”
Section: Isolation and Culture Of Hadscsmentioning
confidence: 99%
See 1 more Smart Citation
“…hADSCs in the third passage were used for the following experiments. Adipogenic and osteogenic differentiation of hADSCs was performed as described earlier [23,24]. hADSCs from three different individuals were used as biological replicates.…”
Section: Isolation and Culture Of Hadscsmentioning
confidence: 99%
“…Recently, several miRNAs have also been identified to be responsible for the balance of adipogenesis and osteogenesis. Overexpression of miR-204, miR-17-5p, and miR-106a suppresses osteoblast differentiation and promotes adipocyte differentiation [23,24]. In contrast, miR-637 has an opposite effect, suggesting that adipocyte and osteoblast differentiation are tightly regulated by specific miRNAs in hMSCs [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several miRNAs were found to be involved in either osteogenesis or adipogenesis (8)(9)(10)(11)(12). However, most of these miRNAs have only been investigated in vitro, and their functional roles in the pathophysiological mechanisms responsible for age-related bone loss and accumulation of fat in bone marrow remain to be established.…”
Section: Introductionmentioning
confidence: 99%
“…45 Although previous studies have shown that miR-148a and miR-17-5p also influence adipocyte differentiation 37 and regeneration, the function of miR-148a and miR-17-5p in the goat mammary gland is unknown. Therefore, the main purpose of the present work was to investigate the synergistic role that miR-148a and miR-17-5p play in the control of mammary cell lipid metabolism using primary goat mammary epithelial cells (GMEC).…”
Section: Introductionmentioning
confidence: 99%